2005
DOI: 10.1590/s0100-67622005000200016
|View full text |Cite
|
Sign up to set email alerts
|

Riparian vegetation affected by bank erosion in the Lower São Francisco River, Northeastern Brazil

Abstract: Changes in the hydrological regime of the Lower São Francisco River, located in Northeastern Brazil have brought negative environmental impacts, jeopardizing the flora and fauna of a global biodiversity hotspot, due to implementation of hydroelectric power dams and surface water withdrawal for irrigation in public and private perimeters. Remnants of the riparian stratum associated to the riverbank destabilization in six fragments were studied by surveying trees, shrubs, herbs, and aquatic species. The calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
17

Year Published

2008
2008
2025
2025

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 6 publications
1
11
0
17
Order By: Relevance
“…In the present study, the marginal habitat with natural riparian vegetation showed a greater array of habitat elements, such as macrophytes and underwater structures. The overall lower littoral depths in the study sites where the natural riparian cover was removed is in accordance with other studies (Holanda et al 2005) which indicate that the removal of the riparian vegetal cover may lead to bank destabilization and increased erosion and sedimentation in the aquatic habitat. In the present study, a high proportion of sand and small gravel in the aquatic substrate composition in areas where the riparian cover was removed are an indication that the exposure of the soil and the consequent erosion are adding coarse sediments to the substrate.…”
Section: Areasupporting
confidence: 92%
“…In the present study, the marginal habitat with natural riparian vegetation showed a greater array of habitat elements, such as macrophytes and underwater structures. The overall lower littoral depths in the study sites where the natural riparian cover was removed is in accordance with other studies (Holanda et al 2005) which indicate that the removal of the riparian vegetal cover may lead to bank destabilization and increased erosion and sedimentation in the aquatic habitat. In the present study, a high proportion of sand and small gravel in the aquatic substrate composition in areas where the riparian cover was removed are an indication that the exposure of the soil and the consequent erosion are adding coarse sediments to the substrate.…”
Section: Areasupporting
confidence: 92%
“…Estradas, lotes residenciais e agrícolas têm sido destruídos pelo acelerado processo erosivo levantado em 57 focos, caracterizado pela desestabilização dos taludes nas margens do rio São Francisco, conforme relato de Casado et al (2002) e Holanda et al (2005).…”
Section: Introductionunclassified
“…Os processos erosivos nas margens de rios, acentuados ou não, pela retirada da mata ciliar, são manifestações mais perceptíveis da complexa readaptação da morfologia do canal em busca de uma nova estabilização e das modificações na dinâmica do sistema fluvial (HOLANDA et al, 2005;HOLANDA et al, 2009). Sabe-se que as matas ciliares podem atuar como redutor do assoreamento, sendo um importante suporte de segurança para o equilíbrio do ecossistema e suas relações essenciais (CASTRO et al, 2013).…”
Section: Ausência De Mata Ciliarunclassified